ISLAMIC EDUCATION AS A SOCIAL INSTITUTION IN SOCIAL CHARACTER FORMATION AND INCLUSIVE HUMAN DEVELOPMENT: A LITERATURE REVIEW - Firmansyah; Ani Aryati (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Inclusive human development emphasizes not only economic capacity or individual skills, but also the quality of social relations, inclusive attitudes, and the ability to live together in diversity. Amidst rising intolerance, identity conflicts, and weakening social solidarity, Islamic education has strategic potential as a social institution that shapes social character based on the values of justice, empathy, tolerance, ukhuwah (brotherhood), deliberation, and social responsibility. This study aims to synthesize academic literature related to the role of Islamic education in shaping social character and its contribution to inclusive human development. The method used is a Systematic Literature Review (SLR) with descriptive-qualitative analysis of 12 recent studies in the 2016–2026 period from reputable national and international journals and research reports. The results show that Islamic education is capable of internalizing moral and social values through curriculum, social interaction, and institutional culture, as well as developing social capabilities such as empathy, cooperation, and appreciation for diversity. However, the application of social values is often limited to passive tolerance and normative approaches, so that active involvement in social justice is not yet optimal. These findings emphasize the need to reposition Islamic education from merely shaping individual piety to building an inclusive, civilized collective social character oriented towards substantive social solidarity, while also providing conceptual guidance for the development of Islamic education policies and practices.